1883 Wash. Sess. Laws 161, An Act to Incorporate the City of Ellensburgh, ch. 2, § 20. - (:unkn) unknown (My University, 1883)
The city of Ellensburg shall have power to prevent injury or annoyance from anything dangerous, offensive, or unhealthy . . . to regulate the transportation storing and keeping of gunpowder and other combustibles and to provide or license magazines for the same[.]
Keywords: GUNPOWDER - STORAGE